The effects of divorce risk on the labour supply of married couples - Kerry L. Papps (Institute for the Study of Labor (IZA), 2006)
This paper presents a model of lifetime utility maximisation in which expectations of future marital transitions play a role in the determination of work hours. Married people with spouses who earn more are predicted to devote additional time to the labour market when they are confronted with a high likelihood of divorce and vice versa. Similarly, work hours should be positively associated with marriage probability for those single people who expect to marry a higher earning spouse. These predictions are tested using data from the National Longitudinal Survey of Youth 1979. Marriage and divorce probabilities are calculated from Cox proportional hazard models and are included in regressions of annual hours. Married women are found to work more when they face a high probability of divorce. This relationship holds both over an individual's life-cycle and across people with different inherent risks of divorce. Similar results are found when a woman's happiness with her marriage is used as a proxy for divorce risk.
urn:nbn:de:101:1-2009040623
Keywords: 330